On the role of the ECB's collateral framework in preventing fire sales - Natalia Podlich (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In this paper, I analyze the impact of the extension of the ECB s collateral framework on securities sales. In addition, I evaluate the impact of different macroeconomic and bank-specific characteristics on banks selling behavior. At this, I distinguish between healthy banks and banks rescued from the German government hypothesizing that distressed banks manage sales of their assets differently. My analysis is based on quantile regressions for panel data containing securities holdings of 27 German banks, which allows an assessment of extremely large sales. Such selling behavior could cause a collapse of prices and lead to fire sales adversely impacting other financial institutions. I find clear evidence that the ECB s collateral framework has a stabilizing impact on sales of assets, especially for impaired banks and during the crisis the relationship is significant.
Keywords: B26; C21; E58; 330